Active Food Packaging Based on Coconut Coir Pulp with the Addition of Antimicrobial Oleoresin Substance from Ginger Dregs - Halimah Nisa Septiani; Amelia Regita Utami; Ananda Salsabilla Fahma Putri; Rafli Zulfa Kamil (Journal of Applied Food Technology, 2022)
The development of food packaging innovations is ongoing, from materials to varied shapes and designs. Paper packaging is one of the various types of packaging that are widely used as an alternative to plastic packaging. However, the high use of paper can damage the environment, such as deforestation and reduction of green land. Alternative raw materials for making paper need to be studied further, and the addition of active ingredients will be an added value compared to ordinary paper packaging. This narrative review will examine the potential of active food packaging from coconut fiber and the addition of ginger pulp oleoresin. Coconut coir is waste from coconut production that is underutilized, while 25% of one coconut is produced from waste in the form of coconut coir. Coconut coir can replace wood's cellulose fibers to manufacture biodegradable, environmentally friendly paper. Ginger flesh contains oleoresin as an antimicrobial agent. Oleoresin is a mixture of essential oils and resins obtained by extraction. Adding these antimicrobial substances will produce active packaging that effectively handles and prevents contamination and microbial growth in food. Therefore, paper made from coconut coir pulp with the addition of oleoresin has the potential to be developed into active food packaging as an effort to conserve the environment and utilize waste.